2000
DOI: 10.1891/0886-6708.15.4.389
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Stalking Victimization

Abstract: This article empirically studies the phenomenon of stalking and its victims by utilizing a random sample of college students at a large public University. The study found that 25% of the women and 11% of the men had been stalked at some point in their lives and that six percent were currently being stalked. Additionally, the study found that the majority of stalking victims are women who are stalked by male offenders. The sample reported being stalked for an average of 347 days and having engaged in a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
164
4
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(187 citation statements)
references
References 0 publications
11
164
4
8
Order By: Relevance
“…Studies show higher rates of stalking incidents among college-aged people than in the general population (Wilcox, Jordan & Pritchard, 2007), and the prevalence rate of victimization is between 10 and 30% (Amar, 2006;Bjerregaard, 2000;Fischer, Cullen & Turner, 2002;Haugaard & Seri, 2003;Coker, Sanderson, Cantu, Huerta, & Fadden, 2008 Additionally, the introduction of this law increased the public's knowledge and awareness (De Fazio, Sgarbi, Moore & Spitzberg, 2015) of stalking, that is currently on the public agenda.…”
Section: Current Workmentioning
confidence: 99%
“…Studies show higher rates of stalking incidents among college-aged people than in the general population (Wilcox, Jordan & Pritchard, 2007), and the prevalence rate of victimization is between 10 and 30% (Amar, 2006;Bjerregaard, 2000;Fischer, Cullen & Turner, 2002;Haugaard & Seri, 2003;Coker, Sanderson, Cantu, Huerta, & Fadden, 2008 Additionally, the introduction of this law increased the public's knowledge and awareness (De Fazio, Sgarbi, Moore & Spitzberg, 2015) of stalking, that is currently on the public agenda.…”
Section: Current Workmentioning
confidence: 99%
“…2 Researchers investigating the prevalence of stalking among college students report substantially higher rates of victimization, typically between 6% and 27% (Logan, Leukefeld, & Walker, 2000;McCreedy & Dennis, 1996). Average rates of stalking victimization range from 13% to 30% for female college students (Fisher, Cullen, & Turner, 2002;Fremouw, Westrup, & Pennypacker, 1997) and from 11% to 19% for male college students (Bjerregaard, 2000;Haugaard & Seri, 2001). While a growing body of literature has examined stalking victimization among adult and college student samples, the prior literature sampling children and adolescents is sparse.…”
Section: Participation In Offending and Victimizationmentioning
confidence: 99%
“…Stalking has only recently been recognized as a criminal offense (Bjerregaard, 2000). Celebrity victims of stalking initially captured media attention, which quickly lead to an unprecedented outbreak of legal action against the perpetration of unwanted pursuit behavior (Perez, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, when the focus of the research is shifted from stalkers to victims, the results change markedly, demonstrating how differently the perception of stalking is between the stalker and the victim. For example, when Bjerregaard 29 administered a questionnaire to 761 US college students aged 18-25 years (65% women, 35% men), he found that 10.9% of the men (29/267) claimed to be victims of stalking, and that in two out of three of these cases, the stalker was a woman. Interviewing 1490 college students, Fox et al 30 discovered that 30% of the victims of stalkers were men.…”
Section: Young Stalkersmentioning
confidence: 99%
“…Previously, a slightly lower percentage (about 20%) had emerged from research by Bjerregaard. 29 Morgan 31 recently investigated the stalking phenomenon among students and faculty members. Interviews in the faculty (52 members, 55.7% women and 44.3% men) identified 87 cases of students who had stalked a professor and, interestingly, nearly half (48.27%) were women (aged 25.2 ± 5.9 years).…”
Section: Young Stalkersmentioning
confidence: 99%